Zastosowanie metod aglomeracyjnych i modelowania wektorowo-autoregresyjnego w analizie przestrzenno-czasowej rynku pracy w Polsce - Rozpędowska-Matraszek, Danuta; Lewandowska, Karolina (Application of aggregation and vector-autoregressive modeling methods in spatiotemporal analysis of labor market in Poland, 2006)
The results of spatiotemporal analysis of economic conditions of labor market in Poland are presented in this paper. The empirical analysis was conducted using quarterly average income, rate of unemployment, rate of inflation and work efficiency data in 1997-2004. Individual characteristics of each administrative region were taken into account. Methods of multi-scale comparison analysis were used for aggregation of statistical data. The next step was to build econometric models describing labor market in Poland using unbalanced panel model and vector-autoregressive model for spatiotemporal sample.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 435-444